(untitled) (Eureka Journal of Humanities and Social Research, 2026)
States are increasingly embedding climate considerations in their contracts with private parties in pursuit of their domestic and international targets and commitments. Such contracts, referred to as public contracts, constitute a form of "soft power" for governments seeking to advance environmental protection and climate regulation. While contractors willingly make promises to engage in good practices, the actual performance of sustainability obligations is questionable, as little impact measurement is conducted. Recognizing the gap between the mere introduction of climate goals and their enforcement, this paper aims to explore why this gap occurs and examine ways to bridge it.